2013
DOI: 10.1016/j.foodres.2013.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Brewer's spent grain from different types of malt: Evaluation of the antioxidant activity and identification of the major phenolic compounds

Abstract: a b s t r a c t Keywords:Brewer's spent grain Microwave-assisted extraction Polyphenols Antioxidant activity Kilning temperature HPLC-DAD/ESI-MS/MS analysis The antioxidant activity and phenolic composition of brewer's spent grain (BSG) extracts obtained by microwave-assisted extraction from two malt types (light and dark malts) were investigated. The total phenolic content (TPC) and antioxidant activity among the light BSG extracts (pilsen, melano, melano 80 and carared) were significantly different (p b 0.05… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
96
4
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 125 publications
(115 citation statements)
references
References 33 publications
9
96
4
6
Order By: Relevance
“…Therefore, the differences observed for pilsen and black BSG extracts can be ascribed to the different composition of the extracts. Ferulic and p-coumaric acids are well known phenolic compounds present in high concentrations in BSG (Moreira et al, 2013). Moreover, previous studies have demonstrated that ferulic acid (FA) protects DNA against oxidative damage caused by H 2 O 2 , as measured by the comet assay (Wang, Sun, Cao, Song, & Tian, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, the differences observed for pilsen and black BSG extracts can be ascribed to the different composition of the extracts. Ferulic and p-coumaric acids are well known phenolic compounds present in high concentrations in BSG (Moreira et al, 2013). Moreover, previous studies have demonstrated that ferulic acid (FA) protects DNA against oxidative damage caused by H 2 O 2 , as measured by the comet assay (Wang, Sun, Cao, Song, & Tian, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…BSG samples used in this work were kindly supplied by Unicer -Bebidas de Portugal, S.A. (S. Mamede de Infesta, Portugal) and obtained from barley malt samples supplied by Os Três Cervejeiros, Lda (Porto, Portugal). BSG samples investigated in this work were chosen according to the more pronounced differences in total phenolic content and antioxidant activity, evaluated in a previous work (Moreira et al, 2013), and correspond to BSG samples obtained from pilsen and black malts. Pilsen malt produces very light colored, clean and crisp worts and is used as base malt for all beer styles.…”
Section: Chemicals and Samplesmentioning
confidence: 99%
See 3 more Smart Citations